(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article examines the modern directions of agricultural development in Uzbekistan, particularly the introduction of innovative technologies, efficient use of land and water resources, and the modernization of the agrarian sector. It also substantiates the importance of ensuring food security, developing cluster systems, and widely implementing the concept of “smart agriculture.” Based on the research findings, scientific recommendations and proposals aimed at improving the efficiency of the agricultural sector have been developed.